Psych 101 psychology facts, basics, statistics, tests, and more! - Kleinman, Paul
"Too often, textbooks turn the noteworthy theories, principles, and experiments of psychology into tedious discourse that even Freud would want to repress. Psych 101 cuts out the boring details and statistics, and instead, gives you a lesson in psychology that keeps you engaged - and your synapses firing. From personality quizzes and the Rorschach Blot Test to B.F. Skinner and the stages of development, this primer for human behavior is packed with hundreds of entertaining psychology basics and quizzes you can't get anywhere else. So whether you're looking to unravel the intricacies of the mind, or just want to find out what makes your friends tick, Psych 101 has all the answers - even the ones you didn't know you were looking for"--P. [4] of cover.